2011
DOI: 10.1080/07481187.2011.573176
|View full text |Cite
|
Sign up to set email alerts
|

Ageism and Risk-Taking in Young Adults: Evidence for a Link Between Death Anxiety and Ageism

Abstract: The authors investigated the relationship between ageism and risk-taking in young adults. They hypothesized that young adults may attempt to distance themselves from their future older selves and from an awareness of their mortality by seeking out experiences that make them feel strong, energetic, and invulnerable (i.e., experiences involving risk-taking). We report a study whose results confirmed the hypothesis. Our study involved 408 undergraduates (226 women, 182 men) who completed the Centers for Disease C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…From this perspective, ageist attitudes and behaviors directed toward older adults are perpetuated in an effort to reduce anxiety by distancing oneself from the threatening prospects of late adulthood. Indeed, evidence has shown that young adults' ageist attitudes and behaviors were related to risktaking and death anxiety, consistent with the view that ageism is a response to mortality awareness (see Popham, Kennison, & Bradley, 2011a, 2011b.…”
supporting
confidence: 60%
“…From this perspective, ageist attitudes and behaviors directed toward older adults are perpetuated in an effort to reduce anxiety by distancing oneself from the threatening prospects of late adulthood. Indeed, evidence has shown that young adults' ageist attitudes and behaviors were related to risktaking and death anxiety, consistent with the view that ageism is a response to mortality awareness (see Popham, Kennison, & Bradley, 2011a, 2011b.…”
supporting
confidence: 60%
“…One paper reported an analysis of discrimination due to age or physical appearance using a subset of US African Americans in the Panel Study on Income Dynamics—Transition to Adulthood Study (Madkour et al, 2015); however, results found no association between either type of discrimination and the study’s main outcome, heavy episodic drinking. Another paper looked at ageist attitudes and behaviors among college students at a single US university and their relationship to alcohol use (Popham, Kennison, & Bradley, 2011). Results showed a conditional relationship by gender, such that both aspects of ageism were correlated with drinking frequency and recent binge episodes in young men but not young women.…”
Section: Resultsmentioning
confidence: 99%
“…Stereotyping or stigmatizing older adults helps younger people to distance themselves from their future self, thus allaying their existential anxiety (Martens et al, ; Nelson, ; Snyder & Meine, ). Intriguingly, ageism related to existential anxiety can promote sensation‐seeking and risky behaviours, as ageist individuals attempt to buffer awareness of their mortality by making themselves feel strong, energetic, and invulnerable (Levy & Myers, ; Popham, Kennison, & Bradley, , ). Consistent with this possibility, younger adults who have close positive relationships with older adults hold less negative attitudes about ageing and also engage in less risk taking in everyday life (Kennison & Ponce‐Garcia, ).…”
Section: Discussionmentioning
confidence: 99%